Performance factors that negatively influence shooting efficiency in women’s basketball - Vencúrik, Tomáš; Milanović, Zoran; Lazić, Anja; Li, Feng; Matulaitis, Kęstutis; Rupčić, Tomislav (Frontiers in Physiology, 2022)
The purpose of the present study was to examine the influence of selected factors (possession duration, game quarter, defensive pressure, shooting distance from the basket, and heart rate level) on shooting efficiency on Under-19 (U19) and senior level of women’s basketball competition (2nd division). The analysis procedures included five U19 and six senior-level games, containing 224 and 252 shooting attempts, respectively. Binary logistic regression identified the opponent's defensive pressure and shooting distance from the basket as significant predictors of shooting efficiency in both categories. When defensive pressure was high, the chance for the missed shot was 3.5 (95% CI; 1.43–8.52) and 3.19 (95% CI; 1.4–7.26) times more likely than it was under the minimum defensive pressure for U19 and senior category, respectively. Shooting efficiency significantly decreased when the horizontal distance from the basket increased. In U19, a chance for a missed shot was 4.63 (95% CI; 2–10.712) and 5.15 (95% CI; 1.91–13.86) times higher for medium and long-distance (respectively), compared to short-range shooting. In the senior category, the chance for the missed shot was 3.9 (95% CI; 1.83–8.31) and 3.27 (95% CI; 1.43–7.52) times higher for medium and long-distance (respectively) when compared to a short distance. The possession duration, game quarter, and heart rate level were identified as insignificant predictors. Therefore, the aforementioned findings suggest that basketball players and coaches may benefit from designing training sessions where the defender puts pressure on the shooting player as in a real game situation and balanced the frequency of shooting from different distances from the basket.